IMPLEMENTASI NILAI-NILAI SILA PANCASILA DALAM MENGHADAPI TANTANGAN ZAMAN MODERN - Awal Ramadhan; Rani Septiani; Nadila Maharani; Ratna Oktaviani (Educatus, 2025)
Pancasila, as the foundation of the Indonesian state, embodies fundamental values in shaping the character and identity of the nation. In the modern era, characterized by technological advancements, globalization, and rapid social changes, the challenges of implementing the values of Pancasila have become increasingly complex. This research aims to explore how the values of each principle of Pancasila can be applied in the context of everyday life amidst various contemporary challenges. The methods used in this study include literature review and interviews with various stakeholders, including educators, community leaders, and the younger generation. The findings indicate that although there are obstacles such as the influence of foreign cultures and a lack of understanding of Pancasila's values, there are opportunities to strengthen implementation through education based on Pancasila values and the use of information technology. This study recommends the need for synergy between the government, society, and educational institutions to integrate Pancasila values into various aspects of life, thereby building a character-driven society with a national perspective in the modern era.